Are New Biomarkers Useful in the Diagnosis of Meningitis in Adults?. (4th October 2017) - Aksoy, Firdevs; Yilmaz, Gürdal; Aydin, Nurten Nur; Kaya, Selcuk; Karahan, Süleyman Caner; Koksal, Iftihar
Abstract: Background: Meningitis is infection of the central nervous system with high mortality and morbidity in adults. Markers for diagnostic purposes can therefore be useful guides in differential diagnosis. Procalcitonin (PCT), platelet distribution width (PDW) and red blood cell distribution width (RDW) can be easily calculated with automated blood systems, and have been regarded as biomarkers showing inflammation in infection-related diseases. The purpose of this study was to determine the diagnostic significance of these biomarkers in adult meningitis. Methods: This study was a retrospective investigation. Diagnosis of meningitis was based on clinical findings and microbiological and biochemical investigations of CSF specimens. Patients' white blood cell count (WBC), C-reactive protein (CRP), PDW, RDW and PCT levels at time of presentation were compared. P < 0.05 was regarded as statistically significant. Results: 137 patients were assessed. Ninety-five patients had acute bacterial meningitis (ABM), 17 had aseptic meningitis (AM) and 25 had chronic meningitis (CM). When patients were evaluated by age, AMB was more common in the elderly and AM in the young ( P < 0.05). CRP and PCT levels at presentation were significantly higher in AM than in AM and CM ( P < 0.05). WBC levels differed statistically significantly between ABM and CM ( P < 0.05). PDW levels were significantly higher in AM then in CM ( P < 0.05). RDW was statistically significantly higher in CM than in ABM and AM ( P < 0.05). When ROC analysis was performed to differentiate ABM from the other forms (table). Correlation analysis between CSF biochemistry and biomarkers revealed that PCT was positively correlated with CRP, PDW and CSF protein and negatively correlated with CSF glucose. Conclusion: Our results suggest that PCT and CRP have diagnostic characteristics in favor of ABM at differential diagnosis in cases in which LP is contraindicated and/or CSF examination cannot be performed immediately or the agent cannot be identified. WBC and RDW can be useful guides in differentiating ABM from CM, and PDW and RDW in differentiating CM from ABM and AM. Disclosures: All authors: No reported disclosures.